Legislative technique as the main precondition of efficiency of legislative activity (Journal of actual problems of jurisprudence, 2018)
The article discusses the main issues related to the process of creating legal acts, reveals the scientific concepts associated with legal equipment, methods and principles used in the creation and adoption of normative legal acts. Accordingly, disclosed the methods used in formulating the text of a legal act – are important elements of the legislative technique, as logic, style and language of the law, their significance and role in shaping the quality of the laws.Key words: legislative technique, legal-norm act, legislation, legislator, the language of the law, style of law, legal terminology, scientific conception.